Food Habit Associated Mycobiota Composition and Their Impact on Human Health - Shankar, Jata (Frontiers in Nutrition, 2021)
Mycobiota is not only associated with healthy homeostasis in the human gut but also helps to adapt to the environment. Food habits, alcohol consumption intake of probiotics, and contaminated food with a mycotoxin, often lead to the alteration in the mycobiota. Impaired immunity of the host may affect fungal symbiosis leading to mycosis. The human gut adapts to the commensalism fungi belong to the phylum Ascomycota and Basidiomycota. Diet habits such as plant-or animal-based, phytoestrogens enriched plant products, fat-rich diets also influence the colonization of certain fungal species in the mammalian gut. Food habits or mycotoxin-contaminated food or fungal peptides influence bacterial-fungal interaction and human health. The mycobiota population such as Fusarium, Humicola, Aspergillus, and Candida are altered due to alcohol intake leading to alcoholic liver disease. The role of associated gut mycobiota due to irregular bowel habits or lifestyle change leads to inflammatory bowel disease. We observed Saccharomyces, Aspergillus, Fusarium, Cladosporium, Candida, and Malassezia were the common genus in the human mycobiota. Thus, the mini-review focuses on how diet habits, alcohol intake, etc., influence mycobiota composition that may affect the immune system or overall health.